Walking Cadence and Mortality Among Community-Dwelling Older Adults - Brown, Justin C. (Springer US, 2014)
BACKGROUND: Older adults are encouraged to walk ≥100 steps∙minute(−1) for moderate-intensity physical activity (i.e., brisk walking). It is unknown if the ability to walk ≥100 steps∙minute(−1) predicts mortality. OBJECTIVE: To determine if the ability to walk ≥100 steps∙minute(−1) predicts mortality among older adults. DESIGN, SETTING, AND PATIENTS: A population-based cohort study among 5,000 older adults from the Third National Health and Nutrition Survey (NHANES III; 1988–1994). Vital status and cause of death were collected through December 31, 2006. Median follow-up was 13.4 years. Average participant age was 70.6 years. MEASUREMENTS: Walking cadence (steps∙minute(−1)) was calculated using a timed 2.4-m walk. Walking cadence was dichotomized at 100 steps∙minute(−1) (≥100 steps∙minute(−1) versus <100 steps∙minute(−1)) to demarcate the lower threshold of absolutely defined moderate-intensity physical activity. Walking cadence was also analyzed as a continuous variable. Predicted survival was compared between walking cadence and gait speed. The primary outcome was all-cause mortality. Secondary outcomes included cardiovascular-specific and cancer-specific mortality and mortality from other causes. RESULTS: Among 5,000 participants, 3,039 (61 %) walked ≥100 steps∙minute(−1). During follow-up, 3,171 subjects died. In multivariable-adjusted analysis, ability to walk ≥100 steps∙minute(−1) predicted a 21 % reduction in all-cause mortality (hazard ratio [HR], 0.79; 95 % confidence interval [95 % CI], 0.71–0.89, p < 0.001). Each ten-step increase in walking cadence predicted a 4 % reduction in all-cause mortality (HR, 0.96, [0.94–0.98], p < 0.001). In secondary analyses, ability to walk ≥100 steps∙minute(−1) predicted reductions in cardiovascular-specific mortality (HR, 0.79 [0.67–0.92], p = 0.002), cancer-specific mortality (HR, 0.76 [0.58–0.99], p = 0.050), and mortality from other causes (HR, 0.82 [0.68–0.97], p = 0.025). Predicted survival, adjusted for age and sex, was not different using walking cadence versus gait speed. LIMITATIONS: Walking cadence was a cross-sectional measurement. CONCLUSIONS: The ability to walk ≥100 steps∙minute(−1) predicts a reduction in mortality among a sample of community-dwelling older adults.